The Influence of Human Resources, Utilization of Information Technology, and Understanding of Accrual-Based Accounting on the Quality of Financial Reports: Pengaruh Sumber Daya Manusia, Pemanfaatan Teknologi Informasi, dan Pemahaman Akuntansi Berbasis Akrual Terhadap Kualitas Laporan Keuangan - Elmas, Alif Kharisma; Biduri, Sarwenda (Indonesian Journal of Law and Economics Review, 2018)
This study aims to determine the effect of human resources (X1) on the use of information technology (X2) and the understanding of accrual-based accounting (X3) on the quality of financial statements (Y) in the Sidoarjo regency government. This study uses quantitative research methods. The sample in this study were 31 respondents with the slovin formula sampling technique. The analytical tool used is the analysis of multiple linear regression tests, t test, F test and coefficient of determination (R²) using SPSS 18 software applications. The results of this study indicate that the tested data is valid and reliable. Based on the t test and the F test, it shows that human resources, the use of information technology and the understanding of accrual-based accounting have a partial or simultaneous effect on the quality of local government financial reports. Variables of human resources, utilization of information technology, and understanding of accrual- based accounting have an influence on the quality of financial statements of 37.5% while the remaining 62.5% is explained by other variables.